Analyzing The Role of Content in Building Brand Image The Digital Era: a Systematic Literature Review - Asvina; Kurniawan, Muhammad Agus; Panjaitan, David; Nisa, Khairun (Journal of Business and Behavioural Entrepreneurship, 2025)
The digital era has driven a significant transformation in brand marketing strategies, with content marketing emerging as a key approach in building brand image. This study aims to analyze the role of content marketing in shaping brand image in the digital age using the Systematic Literature Review (SLR) method, based on the PRISMA 2020 framework. A total of 31 journal articles published between 2020 and 2025 were thoroughly reviewed. The findings indicate that content marketing not only directly influences brand perception but also strengthens brand image through the mediating roles of brand awareness, electronic word-of-mouth (e-WOM), and user-generated content (UGC). Content strategies that are emotional, informative, and personalized have been shown to enhance consumer engagement and stimulate purchase intention. This study concludes that the success of content marketing lies in its ability to build a strong brand image through relevant, consistent, and long-term value-driven digital communication.